1904
DOI: 10.1515/bchm2.1904.42.1-2.121
|View full text |Cite
|
Sign up to set email alerts
|

Brenztraubensäure unter den Spaltungsprodukten der Proteinstoffe.

Abstract: In dieser Zeitschrift hat F. Suter 1 ) die Frage behandelt, ob Brenztraubensäure ein Spaltungsprodukt von Hornsubstanz sei, und sie verneinend beantwortet. Frische Tyrosinmutterlauge wurde mit Schwefelsäure stark angesäuert und mit einer Mischung von Äther und Alkohol extrahiert. Der Rückstand der ätherischen Lösung wurde mit Wasser aufgenommen und mit Quecksilberchlorid gefällt; das Filtrat wurde mit Schwefelwasserstoif behandelt; eine Bildung von Thiomilchsäure konnte weder durch Prüfung mit Quecksilberchlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1911
1911
1942
1942

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This explanation was obtained by investigating the alcoholic mother liquors from which the preparation had been recrystallized. These yielded a preparation with the composition of leucine that had a specific rotation of [a]® = +28.1°(whereas Z-leucine has [a]" = +17.3°) in 22 per cent hydrochloric acid and which was weakly dextrorotatory in water (Z-leucine is levorotatory); it was soluble in only 30 parts of water at 19°. This material was obviously entirely different from Schulze's Z-leucine.…”
Section: Ch-nhx Ch-nhxmentioning
confidence: 99%
See 1 more Smart Citation
“…This explanation was obtained by investigating the alcoholic mother liquors from which the preparation had been recrystallized. These yielded a preparation with the composition of leucine that had a specific rotation of [a]® = +28.1°(whereas Z-leucine has [a]" = +17.3°) in 22 per cent hydrochloric acid and which was weakly dextrorotatory in water (Z-leucine is levorotatory); it was soluble in only 30 parts of water at 19°. This material was obviously entirely different from Schulze's Z-leucine.…”
Section: Ch-nhx Ch-nhxmentioning
confidence: 99%
“…During the early years of the present century a controversy arose as to the identity of the cystine from proteins with that from urinary calculi. Neuberg and Meyer (34) detailed a large number of points of difference between cystine from the two sources and Morner's work (30,31,32), in which he obtained -thiolactic acid from cystine, served to strengthen the view that stone cystine was the disulfide of a-thio-0-aminopropionic acid. Fischer and Suzuki (15), however, showed that Neuberg and Meyer's points of difference were all due to the presence of tyrosine in their preparation of stone cystine, and Gabriel's synthesis (18) of a-thio-|S-aminopropionic acid, which differed in many ways from cysteine, finally settled the matter.…”
Section: Introductionmentioning
confidence: 99%